Tenascin C expression is upregulated in pancreatic cancer and correlates with differentiation. Issue 11 (27th October 2004) - Juuti, A; Nordling, S; Louhimo, J; Lundin, J; Haglund, C
Abstract : Background: Tenascin C is a large, hexameric, extracellular matrix protein that is present during embryonic development but essentially absent in adult tissues. It is involved in remodelling processes, such as wound healing and tumour development. Tissue expression of tenascin C correlates with prognosis in colorectal, cervical, and breast cancer and in carcinoma of the papilla of Vater. Aim: To study the expression of tenascin C in pancreatic cancer and to compare the staining results with the patients' clinicopathological data. Material and methods: Formalin fixed, paraffin wax embedded specimens from 146 patients with pancreatic adenocarcinoma were stained with an anti-tenascin C monoclonal antibody. Results: Tenascin C immunoreactivity was seen in most samples of pancreatic carcinoma: staining was weak in 72 (49%), moderate in 52 (36%), strong in 10 (7%), and negative in 12 (8%) samples. Tenascin C expression correlated with age (⩽ 66 v > 66 years) and poor differentiation (grades 1–2 v 3). There was no correlation between tenascin C expression and survival, clinical stage, tumour size, nodal status, distant metastasis, tumour location, or sex. Conclusion: Tenascin C expression was increased in most pancreatic carcinomas, but contrary to the results in other cancers, it is not a prognostic factor in pancreatic cancer.